Pemilihan Alat Kontrasepsi dalam Rahim (AKDR) pada akseptor Keluarga Berencana - Mita Meilani; Ade Putranto Prasetyo Wijiharto Tunggali (Jurnal Kebidanan, 2020)
Family Planning is the most basic and primary preventive health service effort. One of the acceptable contraceptives in Indonesia is the Contraceptive Intra Uteri Device (IUD), which is the most effective, safe and comfortable contraception for many women. Use of contraception is still dominated by short-term contraceptives, especially injections which reach 31.2% and pills 13.4%. While the level of use of the Long-Term Contraception method, the IUD reaches 4.8%. In 2013, based on the results of the KB prevalence survey with MKJP of 64.6%. Overall, there were still 16 provinces that reached the position of family planning prevalence with MKJP lower than the national figure (> 64.6%). This study aims to determine the relationship of maternal characteristics with the selection of contraceptives Intra Uteri Device (IUD) on family planning acceptors at the Kramatwatu Health Center in Serang, Banten. This quantitative study uses a cross sectional approach with 82  acceptor respondents and uses a check list instrument. The results of the research prove that with the results of statistically significant tests showing that there is a relationship between maternal age, maternal parity, maternal education and occupation with the selection of contraceptives intra uteri device on family planning acceptors with p-value 0.004 <0.05, p-value 0.007 <0 .05, p-value 0.006 <0.05 and p-value 0.007 <0.05. The conclusion in this study there is a relationship between maternal characteristics with the IUD selection so that health workers can optimize counseling about family planning, especially the use of intra uterine devices (IUD).